2020
DOI: 10.1186/s12951-020-00631-4
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Iron oxides nanoparticles (IOs) exposed to magnetic field promote expression of osteogenic markers in osteoblasts through integrin alpha-3 (INTa-3) activation, inhibits osteoclasts activity and exerts anti-inflammatory action

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Study have shown that IONPs could be rapidly magnetized under exposed to an SMF, and the combination of IOPNs and SMF have a synergistically enhance or inhibit effect on the differentiation of osteoblasts and osteoclasts. 147 Marycz et al 148 showed a-Fe 2 O 3 /g-Fe 2 O 3 nanocomposite (IOs) combined with 0.2 T SMF enhance the expression of osteogenic marker OPN, OCN, and Coll-1 in MC3T3 osteoblasts by activating integrin alpha-3 (INTa-3). IONPs-loaded bovine serum albumin (Fe 3 O 4 /BSA) particles exposed to 1 T SMF enhanced ALP activity and the expressions of COL-1 and OCN, and increased the osteogenic differentiation of MSCs.…”
Section: Reviewmentioning
confidence: 99%
“…Study have shown that IONPs could be rapidly magnetized under exposed to an SMF, and the combination of IOPNs and SMF have a synergistically enhance or inhibit effect on the differentiation of osteoblasts and osteoclasts. 147 Marycz et al 148 showed a-Fe 2 O 3 /g-Fe 2 O 3 nanocomposite (IOs) combined with 0.2 T SMF enhance the expression of osteogenic marker OPN, OCN, and Coll-1 in MC3T3 osteoblasts by activating integrin alpha-3 (INTa-3). IONPs-loaded bovine serum albumin (Fe 3 O 4 /BSA) particles exposed to 1 T SMF enhanced ALP activity and the expressions of COL-1 and OCN, and increased the osteogenic differentiation of MSCs.…”
Section: Reviewmentioning
confidence: 99%
“…[ 201 ] It was reported that integrins, the major molecular force transducers, mediated the mechanotransduction process of magnetic nanoparticles and SMF. [ 207a ] RhoA/Rho‐associated kinase (Rho‐kinase/ROCK) and MAPK signaling pathways, which are downstream of integrins, are subsequently activated, facilitating osteogenic differentiation. [ 218 ] Meanwhile, α‐Fe 2 O 3 /γ‐Fe 2 O 3 are not only able to enhance the osteogenic activities of stem cells through activating integrin alpha‐3 (INTα‐3) [ 207a ] but also by upregulating WNT/β‐catenin signaling.…”
Section: Impact Of Magnetic Signalsmentioning
confidence: 99%
“…For example, Fe 3 O 4 was demonstrated to increase the osteogenic differentiation of MC3T3 osteoblasts significantly when exposed to a magnetic field. [ 207 ] Besides, many researchers have combined magnetic nanoparticles with other desirable scaffolds to create nanocomposites with comprehensive properties for biomedical applications. Preparation methods that have been extensively studied include selective laser sintering, [ 208 ] grafting, layer‐by‐layer assembly in combination with electrospinning techniques, [ 209 ] and co‐deposition.…”
Section: Impact Of Magnetic Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 25 ] More importantly, several studies have demonstrated that the combination of Fe 3 O 4 NPs and SMF was more effective than Fe 3 O 4 NPs or SMF alone in bone regeneration. [ 26 ] However, the exact mechanism of synergistic effects of Fe 3 O 4 NPs and SMF on osteogenesis in this context remains to be explored.…”
Section: Introductionmentioning
confidence: 99%